AXIOLOGIZATION CRITERIA OF STUDENTS’ PROFESSIONAL EDUCATION IN THE SYSTEM OF PEDAGOGICAL EDUCATION (Education in the 21st Century, 2023)
Annotation. This article reviews the problem of students' professional education in the system of pedagogical education. An analysis of the scientific literature on the problem made it possible to reveal the essence of professional education, revealed its relevance and showed that insufficient attention is paid to the value aspect of such education and the criteria of axiologisation.The goal of the study is to present and substantiate the main axiologization criteria of the students’ professional education.Based on the goal, the objectives of the study were defined: to consider the axiological approach, the principles that reveal its essence and ensure the axiologization of students' professional education; to highlight and reveal the essence of value consciousness, value orientation, value attitude, value setting and value behavior in the axiologization of future teachers’ professional education as axiologization criteria; to reveal the role of pedagogical values in the axiologization of the process of professional education; to identify the students’ attitude to pedagogical values with the help of a sociological survey; to orient future teachers to a value setting for professional activity based on the formation and development of a value system; to show and substantiate the role of axiologization in professional education as an important means of increasing the effectiveness of future teachers’ training at the HEI.In the course of the axiologization of professional education, students should form: pedagogical values, value consciousness, value attitude, value setting, value orientations, value behavior. Otherwise, we can state that there was no axiologization. Consequently, they are criteria, indicators of the axiologization of professional education.The students’ attitude to different values was revealed with the help of a sociological survey for senior students of SUSh and school teachers of the city of Gyumri, who have no more than three years of experience. The results obtained will make it possible to more effectively organize the processes of formation of pedagogical values and the axiologization of students’ professional education in order to better prepare for future professional activities.In perspective: the results of this study will be reflected in the methodological guideline to determine the content, forms, methods of future teachers’ professional education on an axiological basis.